Mass culture in Japan in the context of globalization - Balaubayeva, Binur; Idrysheva, Zhazira (International relations and international law Journal, 2018)
Currently, Japan is actively promoting itself as a regional center of globalization. On the basis of new global problems Japan seeks to revise its cultural strategy. This is the development of mass culture, as it stimulates the rapid improvement of consumer society and the emergence of new technologies. After that, we can say that sites for anime and manga are growing rapidly. The main problem is the emergence of a new humanitarian image of Japan and its cultural technologies based on ultra-new technologies. Now in Japan the importance and role of cultural exports, which is a form of «soft power» is understood. According to the concept proposed by the Advisory Council on Cultural Diplomacy of Japan, the prevalence of national mass culture is usually seen as a starting point for understanding Japan. Japan is a pioneer in the field of «globalization». Japanese research is a process that dominates, is assimilated and influenced by Japanese culture, than other cultures. Now Japan is a phenomenon in the world of globalization that allows transforming Western cultural values to the East and making maximum efforts to produce products of the national cultural industry and providing new opportunities for a civilized dialogue. Many cultural projects in Japan form global trends in spiritual and material life. As the new regional center of globalization processes Japan is actively promoting the emergence of a new global cultural space, promoting the way of life of millions of people in the West and in the East.